A trait‐based trade‐off between growth and mortality: evidence from 15 tropical tree species using size‐specific relative growth rates. Issue 18 (5th September 2014) - Philipson, Christopher D.; Dent, Daisy H.; O'Brien, Michael J.; Chamagne, Juliette; Dzulkifli, Dzaeman; Nilus, Reuben; Philips, Sam; Reynolds, Glen; Saner, Philippe; Hector, Andy
Abstract A life‐history trade‐off between low mortality in the dark and rapid growth in the light is one of the most widely accepted mechanisms underlying plant ecological strategies in tropical forests. Differences in plant functional traits are thought to underlie these distinct ecological strategies; however, very few studies have shown relationships between functional traits and demographic rates within a functional group. We present 8 years of growth and mortality data from saplings of 15 species of Dipterocarpaceae planted into logged‐over forest in Malaysian Borneo, and the relationships between these demographic rates and four key functional traits: wood density, specific leaf area (SLA), seed mass, and leaf C:N ratio. Species‐specific differences in growth rates were separated from seedling size effects by fitting nonlinear mixed‐effects models, to repeated measurements taken on individuals at multiple time points. Mortality data were analyzed using binary logistic regressions in a mixed‐effects models framework. Growth increased and mortality decreased with increasing light availability. Species differed in both their growth and mortality rates, yet there was little evidence for a statistical interaction between species and light for either response. There was a positive relationship between growth rate and the predicted probability of mortality regardless of light environment, suggesting that this relationship may be driven by a general trade‐off between traits that maximize growth and traits that minimize mortality, rather than through differential species responses to light. Our results indicate that wood density is an important trait that indicates both the ability of species to grow and resistance to mortality, but no other trait was correlated with either growth or mortality. Therefore, the growth mortality trade‐off among species of dipterocarp appears to be general in being independent of species crossovers in performance in different light environments.